2019
DOI: 10.1016/j.tranon.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple Negative Breast Cancers (QNBC) Demonstrate Subtype Consistency among Primary and Recurrent or Metastatic Breast Cancer

Abstract: PURPOSE: Despite the availability of current standards of care treatments for triple negative breast cancer (TNBC), many patients still die from this disease. Quadruple negative tumors, which are TNBC tumors that lack androgen receptor (AR), represent a more aggressive subtype of TNBC; however, the molecular features are not well understood. METHODS: Immunohistochemistry of estrogen receptor (ER), progesterone receptor (PR), HER2, and AR was determined in 244 primary and 630 recurrent/metastatic site biopsies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
(71 reference statements)
0
24
0
Order By: Relevance
“…Age at diagnosis was greater among the LAR subtype [ 3 ] and AR-positive TNBC [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ] in comparison to other subtypes and AR-negative TNBC, respectively. This phenomenon could be attributed to the use of hormonal replacement therapy in postmenopausal patients, or to the more indolent profile of AR-positive tumors, therefore appearing in older patients [ 26 ].…”
Section: Clinical Characteristics Of Ar-positive Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Age at diagnosis was greater among the LAR subtype [ 3 ] and AR-positive TNBC [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ] in comparison to other subtypes and AR-negative TNBC, respectively. This phenomenon could be attributed to the use of hormonal replacement therapy in postmenopausal patients, or to the more indolent profile of AR-positive tumors, therefore appearing in older patients [ 26 ].…”
Section: Clinical Characteristics Of Ar-positive Tnbcmentioning
confidence: 99%
“…A high discordance rate is present in biomarker expression between primary and metastatic lesions [ 14 , 24 ], as well as between primary tumor and recurrent lesion [ 66 ]. Likewise, a significant degree of discordance in biomarkers among all breast cancer subtypes has been studied, with the highest discordance rate among TNBC [ 23 ]. When AR was negative, TNBC discordance rate between primary, metastatic, and recurrent tumor decreased.…”
Section: Prognosismentioning
confidence: 99%
“…Yet another consideration is a switch in hormone receptor status that often follows cancer recurrence, especially so in TNBC, which exhibits elevated metastatic potential. Angajala et al 34 observed an increase in QNBC subtype at second profile status of TNBC that had progressed to a recurrent/metastatic stage. So although AR-positive TNBC exhibited a heterogeneous profile with a greater frequency of being diagnosed as AR negative at an advanced stage, QNBC displayed a more stable phenotype.…”
Section: Introductionmentioning
confidence: 98%
“…So although AR-positive TNBC exhibited a heterogeneous profile with a greater frequency of being diagnosed as AR negative at an advanced stage, QNBC displayed a more stable phenotype. 34 In view of the complex role of AR in BC and the distinctive characterization its presence and absence effects in the TNBC landscape, it is imperative to include AR analysis in routine clinical practice (together with the assessment of ER, PR, and HER2 expression). Because there is little consensus on AR positivity cut-off as determined by immunohistochemistry, a more reliable means of assessment, such as an androgen-driven gene signature, should be depended on instead.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of facilities for early detection, the advent of quadruple negative breast cancer types, and poor access to various treatment methods are the major contributors to increased mortality rates in developing countries (Angajala et al, 2019). Although existing therapies are ef icient, a number of drawbacks and side effects were reported.…”
Section: Introductionmentioning
confidence: 99%